Strategy for Improving The Quality of Ibtidaiyah Madrasah Teachers In The Ministry of Religion, Bandung City - Nani Rohaeni; Ulfiah Ulfiah; Achmad Mudrikah; Sayyid Muhammad Rifqi Noval (Journal of Social Science, 2021)
This research aims to find out the penomena investigated, about the strategy of improving the quality of madrasah ibtidaiyah teachers in the ministry of religion in Bandung. This study uses qualitative approach with descriptive method. This research was obtained through observation techniques, interviews and documentation. Then analyzed using data reduction stages, data display, and data cocclusion. Based on the results of the study showed, that: 1) The objectives of these three Madrasahs refer to the vision of their respective school missions, 2) The implementation in general has been equally conducting activities in accordance with the planned program,3) The problems faced by these three MIS are almost the same, namely related to some teachers who are less competent, minimal financing and inadequate infrastructure 4) As for the solution by Coordinating with other Teachers, Coordinating with the Foundation and Committee, Coaching of Supervisors/PenMad and Active in kkg (Teacher Working Group).